Is Literacy a Function in Determining the Hemispheric Specialization of Language? - Kumar PJ; Purushothama G (Journal of All India Institute of Speech and Hearing, 1970)
The authors of this paper have tried to discuss whether literacy has any emphasis in determining cerebral dominance for language. They discuss the possibilities  of the same, taking evidence from the research  works  which have been done earlier.